Effects induced by periodontal disease on overall quality of life and self-esteem - Simona Santonocito; Giuseppe Palazzo; Francesco Indelicato; Akhilanand Chaurasia; Gaetano Isola (Mediterranean Journal of Clinical Psychology, 2022)
Background and aims: Based on the evidence regarding the relationship between inflammatory processes and stress responses, the present study investigated the association between psychological stress and oral health-related quality of life (OHRQoL) measures related to periodontal disease in adult patients.